(untitled) (Journal of Pathology of Nepal, 2024)
Chronic myelomonocytic leukemia is a clonal stem cell disorder characterized by persistent monocytosis along with myelodysplasia and/or myeloproliferation. According to the World Health Organization 2016 4th edition, Chronic myelomonocytic leukemia is categorized as a myeloproliferative/myelodysplastic disorder and its diagnosis requires the presence of persistent monocytosis and dysplasia involving one or more myeloid cell lineages. Chronic myelomonocytic leukemia is a rare disease with a heterogeneous clinical presentation. Recent progress in the molecular and cellular pathogenesis of Chronic myelomonocytic leukemia has stirred a renewed interest in this clinically heterogeneous disorder. Herein, we report of case of Chronic myelomonocytic leukemia in a 70-years male patient.